ChemInform Abstract: Transition Metal‐Free Direct C—H (Hetero)arylation of Heteroarenes: A Sustainable Methodology to Access (Hetero)aryl‐Substituted Heteroarenes. Issue 8 (February 2016) - Rossi, Renzo; Lessi, Marco; Manzini, Chiara; Marianetti, Giulia; Bellina, Fabio
Abstract: Review: [99 refs.